Pendidikan Inklusi dan Kesetaraan Gender : Suatu Kajian Sistematis Menggunakan Metode PRISMA - R.A. Annita Meilina Ahmadi; Yadi Supriyadi; Ina Herlina; Alfianisa Karromah Sunardi; Kinanti Fadillah Kusuma; Atu Solihah; Ria Asih Mulyani (Lembaga Pengembangan Kinerja Dosen, 2026)
Inclusive education and gender equality are two essential components in creating a learning environment that is fair, equitable, and responsive to student diversity. This article presents a systematic review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach on 28 scientific articles published between 2019 and 2025. The research objective is to map the trends, implementation strategies, barriers, and opportunities for strengthening inclusive education with a gender perspective at the primary and secondary education levels. The results of the analysis indicate that the successful implementation of inclusive-gender education is closely related to gender-responsive teacher competence, family–community support, equitable school policies, and differentiated learning designs. The study also reveals that gender bias and stereotypes remain significant obstacles, while GESI/GEDSI training and pedagogical innovations have proven effective in improving the quality of inclusive education services. This review recommends strengthening the capacity of educators, reformulating school policies, and developing a gender-responsive curriculum as central strategies for achieving sustainable inclusive education.